2018
DOI: 10.1063/1.5012087
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and turbulent flow modes of cold atmospheric pressure argon plasma jet

Abstract: Laminar and turbulent flow modes of a cold atmospheric pressure argon plasma jet are investigated in this work. The effects of the gas flow rate, applied voltage, and frequency on each plasma mode and on intermodal transitions are characterized using photographic, electrical, and spectroscopic techniques. Increasing the gas flow rate increases the plasma jet length in the laminar mode. Upon transition to the turbulent mode, increasing the gas flow rate leads to a decrease in the plasma jet length. The flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…The imaging of the non-thermal APPJ declared that adding oxygen to the plasma accelerates the mode transition from filamentary to diffused mode at lower flow rate values compared to the case of pure argon as illustrated in Figure 3. Normally, the filament is generated inside the diffused plasma at the operation condition 4.5 slpm, 14 kV, and 29 kHz [24]. However, the filament is disappearing by adding oxygen gas.…”
Section: The Effect Of Oxygen Gas Mixing On Acppjmentioning
confidence: 99%
“…The imaging of the non-thermal APPJ declared that adding oxygen to the plasma accelerates the mode transition from filamentary to diffused mode at lower flow rate values compared to the case of pure argon as illustrated in Figure 3. Normally, the filament is generated inside the diffused plasma at the operation condition 4.5 slpm, 14 kV, and 29 kHz [24]. However, the filament is disappearing by adding oxygen gas.…”
Section: The Effect Of Oxygen Gas Mixing On Acppjmentioning
confidence: 99%
“…During the transition, the boundary layer separating the gas flow from ambient air is scattered, enabling the air to mingle with the flowing gas [16]. One can also observe how the form of the jet changes from a plume or a bullet shape when the flow is laminar to a cylindrical glow when the flow mode becomes turbulent [17,18]. This mixing leads to a decrease in the jet's length and influences the jet's temperature, which will be detailed in the next section.…”
Section: The Jet Lengthmentioning
confidence: 99%
“…Since the flow mode explains the relation between the jet's length and the gas flow, one can expect that various parameters may change the jet's behavior as the flow differs. Indeed, it was shown that the length of an argon jet responds differently to the varying flow rate, and even if the same gas is used, the maximum jet length varies depending on the applied voltage [9,18].…”
Section: The Jet Lengthmentioning
confidence: 99%
“…[33] Increasing the applied power to attain the longer plasma length led to thermal instabilities, [34][35][36] whereas increasing the gas flow tends the plasma jet into turbulent operation. [37] This control on plasma jet dimensions could provide additional choice in transporting the generated species remotely to the targets where plasma-treated zone can be isolated from the plasma discharge region in various biomedical and material processing applications. [38] Also, in the view of commercialization of RF cold plasma jets, a thorough knowledge of the influence of vast operating parameters on fundamental discharge characteristics (plasma dimensions, essential species characteristics, plasma parameters [n e , T exc , T g ] etc.)…”
Section: Introductionmentioning
confidence: 99%